STUDY ON UNDERAGE MARRIAGE IN EMPAT LAWANG REGENCY VIEWED FROM THE LAW OF THE REPUBLIC OF INDONESIA NUMBER 16 OF 2019 IN CONJUNCTION WITH LAW NUMBER 1 OF 1974 ABOUT MARRIAGE - Alfha Sulindra; M. Darudin; Sirman Dahwal (Universitas Bengkulu, 2021)
Underage marriage is a marriage bond between a man and a woman, where the age of both or one of them has not reached the limits stipulated in Law of the Republic of Indonesia Number 16 of 2019 in conjunction with Law of the Republic of Indonesia Number 1 of 1974 about Marriage. Underage marriage is one of the legal acts that is not justified by the law of marriage. However, in reality in Empat Lawang Regency it is still practiced, and even the number of underage marriages is still high. The formulation of the problems in this study were: (1) How was the underage marriage in Empat Lawang Regency viewed from the Law of the Republic of Indonesia Number 16 of 2019 in conjunction with Law of the Republic of Indonesia Number 1 of 1974 about Marriage? (2) What were the factors causing the high rate of underage marriage in Empat Lawang Regency? (3) How was the impact of underage marriage on the harmony of domestic life? The research method applied in this study was juridical empirical. The results of this study indicated that: (1) Underage marriage in Empat Lawang Regency had been carried out according to Law of the Republic of Indonesia Number 16 of 2019 in conjunction with Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage, if the prospective husband and wife had not met the requirements as regulated in the Law, then the prospective husband and wife must apply for dispensation to the Religious Court for approval of marriage permits. (2) The factors causing the high rate of underage marriages in Empat Lawang Regency consisted of being pregnant outside of marriage (married by accident), worrying that their child will fall into promiscuity, pressure from parents, lack of economic stability, desire of lasting relationship, family traditions, lack of parental supervision of children, lack of sex education, and parental mindset. (3) The impact of underage marriage on the harmony of household life was the difficulty to form such a harmonious household.